Technology and innovation in Latin America : the need for a turning point - Montiel Méndez, Oscar Javier; Álvarez-Castañón, Lorena del Carmen; Jasso, Javier (Emerald Publishing Limited, 2025)
Technology and innovation are often linked with better ways of doing business, societal improvement and economic growth; the region of Latin America has historically imported its business paradigms from other countries, but now is forging its own path. Technology and Innovation in Latin America gathers scholars from all over Latin America to present their research exploring the dual aspects of technology and innovation and their interrelatedness. On the technology side, chapters delve deep into the debate on R&D, Innovation and Entrepreneurship; Corporate Venturing and Digital Entrepreneurship; Intrapreneurship strategy and processes and more. Technology and Innovation in Latin America offers deep learning about key questions: What are the empirical and theoretical opportunities that emerge in innovation based on territorial capital? How does the context influence the development of innovation policies? How have the dynamics of financing and involvement of financial institutions impacted the support of innovation? Readers will benefit from this being the wide-angle exploration of the region with its varying economies from emerging to transitional, highlighting the role that this unique region can play on the world stage.
Includes index.
Keywords: Technological innovations -- Latin America.; Business & Economics -- Research & Development.; Business innovation.; Research and development management.; elektronické knihy; electronic books